1980
DOI: 10.1073/pnas.77.2.1068
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of polyoma virus mutants able to develop in embryonal carcinoma cells.

Abstract: The close relationships between murine teratocarcinoma stem cells and early embryonic mouse cells are well established, and many of these cell lines are widely used as tools for the study of differentiation (1-3). Among the modifications involved in the differentiation process, the ability of the cell to support the expression of some oncogenic viruses is affected. The undifferentiated murine teratocarcinoma stem cells are refractory to infection with polyoma (Py), simian virus 40 (SV40) (4, 5), minute virus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Rearrangement of the enhancer B domain of polyomavirus may be required to identify the EC host range mutant (12,21,22,25,32,37). The unique property of fPyF9, persistence in an episomal state, seems to be due to box DNA, since the effects of insertion of box DNA in the control region differ from those thus far reported for EC mutants.…”
Section: Discussionmentioning
confidence: 98%
“…Rearrangement of the enhancer B domain of polyomavirus may be required to identify the EC host range mutant (12,21,22,25,32,37). The unique property of fPyF9, persistence in an episomal state, seems to be due to box DNA, since the effects of insertion of box DNA in the control region differ from those thus far reported for EC mutants.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Segal et al (1979) noted that the restrictive interaction of simian virus 40 (SV40) with non-differentiated teratocarcinoma cells was related to failure in viral mRNA splicing. For polyoma virus (Vasseur et al, 1980) and cytomegalovirus (Dutko & Oldstone, 1981), a block in replication at the transcriptional level was reported in undifferentiated embryonal carcinoma cells (ECC). D 'Auriol et al (1981) suggested that the Rauscher murine leukaemia virus proviral DNA failed to integrate into the genome of ECC to account for the restriction in virus replication.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence detection of T-antigen-positive cells was done 60 to 72 h after transfection with plasmid DNA as described above, according to techniques described elsewhere (27). purified by centrifugation in cesium chlorideethidium bromide density gradients.…”
Section: Methodsmentioning
confidence: 99%